2017
DOI: 10.1177/0963721416667444
|View full text |Cite
|
Sign up to set email alerts
|

A Social Psychological Perspective on the Links Between Close Relationships and Health

Abstract: The association between the quality of people’s close relationships and their physical health is well-established. But from a psychological perspective, how do close relationships impact physical health? This article summarizes recent work seeking to identify the relationship processes, psychological mediators and moderators of the links between close relationships and health, with an emphasis on studies of married and cohabitating couples. We begin with a brief review of a recent meta-analysis of the links be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 43 publications
(48 reference statements)
10
113
0
4
Order By: Relevance
“…These relationships need to be high‐quality, characterized by mutual trust, satisfaction, and responsiveness, in order to impart health benefits. Low‐quality relationships, characterized by hostility and conflict, can actually have negative effects on physical health (Farrell & Simpson, ; Slatcher & Selcuk, ). High‐quality relationships can improve health by buffering stress via processes such as social support (Cohen & Wills, ; Hostinar, Sullivan, & Gunnar, ), but positive relationship factors such as perceived partner responsiveness have been found to have direct, main‐effect style impacts on health regardless of level of stress (Slatcher & Schoebi, ; for a review of buffering vs. direct effects models of social support on health, see Cohen & Wills, ).…”
Section: Introductionmentioning
confidence: 99%
“…These relationships need to be high‐quality, characterized by mutual trust, satisfaction, and responsiveness, in order to impart health benefits. Low‐quality relationships, characterized by hostility and conflict, can actually have negative effects on physical health (Farrell & Simpson, ; Slatcher & Selcuk, ). High‐quality relationships can improve health by buffering stress via processes such as social support (Cohen & Wills, ; Hostinar, Sullivan, & Gunnar, ), but positive relationship factors such as perceived partner responsiveness have been found to have direct, main‐effect style impacts on health regardless of level of stress (Slatcher & Schoebi, ; for a review of buffering vs. direct effects models of social support on health, see Cohen & Wills, ).…”
Section: Introductionmentioning
confidence: 99%
“…Again, the cognitive sciences can offer us some insights into Nyangrel's readings of the myth. Scholars of attachment know that, particularly for children, who are the most vulnerable because of their complete dependence on their primary caretakers, comfort, support, and stability are crucial for the flourishing of physically and mentally healthy individuals (Runtz and Schallow 1997;Schore 2003;Slatcher and Selcuk 2017), just as healthy attachment involves parental attunement-the mirroring of the child's behavior through gestures, facial expressions, and voice-in order for children to develop a clear sense of their own selves, to familiarize themselves with their sensations, and to learn to regulate their emotions (Fonagy et al 2002;Gergely and Watson 1999;Holmes 2001), Nyangrel enunciates the positive potential of the ground as motherhood.…”
Section: The Perpetuation Of Trauma and The Conservative Turn Of Thementioning
confidence: 99%
“…Well-being is a broad construct that has been defined in emotional, mental, and physical terms (Diener, Oishi, & Lucas, 2002), and social connectedness may well be an important factor strongly affecting prisoners' well-being especially because prisoners are at high risk of social isolation-from each other and society in general (Nurse, Woodcock, & Ormsby, 2003). Social connectedness, stemming from both close relationships (Holt-Lunstad, Smith, & Layton, 2010;Slatcher & Selcuck, 2017) and social groups (Cruwys et al, 2014;Gleibs et al, 2011;Greenaway, Cruwys, Haslam, & Jetten, 2016;Jetten et al, 2017), has been found to be a powerful predictor of people's physical and mental health. This paper thus considers the role of social ties in promoting the health and well-being of prisoners: in Study 1 we investigate the association between prisoner-to-prisoner relations and well-being, and in Study 2 we investigate the relationship between multiple group memberships (inside and outside prison) and well-being.…”
Section: Health and Well-being In Uk Prisonsmentioning
confidence: 99%